Pengaruh Kompensasi, Motivasi, Komunikasi Dan Beban Kerja Terhadap Semangat Kerja Karyawan Pada PT XYZ Karanganyar - Rista Matdiasih; Esti Dwi Rahmawati; Indra Hastuti (Transformasi: Journal of Economics and Business Management, 2023)
The purpose of this study is to analyze the effect of compensation, motivation, communication and workload on employee morale. This type of research is a quantitative approach using survey methods. Sources of data used are primary data and secondary data. The population in this study are employees of PT XYZ. The number of samples used were 103 employees. The sampling technique uses probability sampling with simple random sampling or simple random sampling. Data collection techniques using a questionnaire. Data analysis in this study used descriptive analysis, multiple linear regression test, t test, f test and coefficient of determination test. The results showed that compensation has a significant effect on morale, motivation has a significant influence on morale, communication has a significant influence on morale and workload has a significant influence on employee morale at PT XYZ. Simultaneously compensation, motivation, communication and workload have a significant influence on employee morale.